Prospects of mango fruit powder production at farm level and its utilisation during mango off-season in Ghana - Edusei, V. O.; Essilfie, G.; Ofosu-Anim, J.; Saalia, F. K.; Eziah, V. (International Journal of Horticultural Science, 2022)
Mango (Mangifera indica) is an important fruit served to customers as fresh-cut fruit, juice, ice cream and yogurts in many fruit juice joints, restaurants and hotels in Ghana. However, the crop’s highly seasonal and perishable nature is a challenge for food processors and farmers. Preservation of the fruit in dry particulate form can serve as a substitute in off-seasons. The study sought to determine mango fruit powder production prospects at the farm level and explore its potential use as a substitute during the off-season. Farmer groups and food enterprises were therefore interviewed. The study showed that Keitt and Kent varieties were the most cultivated varieties because of market demand and high yield. However, an average annual fruit loss of 29.8% at the farm level was observed. Postharvest extension delivery service to farmers is inadequate, and where available, frequency of contact is irregular. A limited number of farmers received training in fruit processing; and few were engaged in transformational value addition activities but were willing to add value through processing into powder. Probit regression analysis showed that a unit increase in training would increase transformational farm level value addition into mango fruit powder by 22.9%. The majority of the food enterprises source fruits within Ghana while 79% experienced mango fruit shortage in the off-seasons. Only a few of the enterprises used mango fruit-based substitutes to serve customers in off-seasons. Probit regression analysis showed that a marginal increase in processors’ use of substitute significantly (p≤0.05) increased willingness to use mango fruit powder as a substitute by 47%. The study has revealed that local production of mango fruit powder could serve as a substitute to fill the seasonal gap in mango supply and also reduce post-harvest losses.